2008
DOI: 10.1186/1471-2407-8-280
|View full text |Cite
|
Sign up to set email alerts
|

Musashi1 modulates cell proliferation genes in the medulloblastoma cell line Daoy

Abstract: Background: Musashi1 (Msi1) is an RNA binding protein with a central role during nervous system development and stem cell maintenance. High levels of Msi1 have been reported in several malignancies including brain tumors thereby associating Msi1 and cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 46 publications
5
83
0
Order By: Relevance
“…28 Silencing of MSI1 in DAOY medulloblastoma cells decreased proliferation and neurosphere formation, and induced differentiation and apoptosis. 29 In the particular case of glioblastoma, we observed that a reduction in MSI1 expression increased apoptosis, decreased proliferation, affected cell cycle regulation, and interfered with adhesion-related functions such as invasion and migration. 13 However, the impact of MSI1 expression on treatment outcome is poorly understood.…”
Section: Discussionmentioning
confidence: 95%
“…28 Silencing of MSI1 in DAOY medulloblastoma cells decreased proliferation and neurosphere formation, and induced differentiation and apoptosis. 29 In the particular case of glioblastoma, we observed that a reduction in MSI1 expression increased apoptosis, decreased proliferation, affected cell cycle regulation, and interfered with adhesion-related functions such as invasion and migration. 13 However, the impact of MSI1 expression on treatment outcome is poorly understood.…”
Section: Discussionmentioning
confidence: 95%
“…Msi-1 is an RNA binding protein which is preferentially expressed in stem-cells, functions as a translational repressor (56)(57)(58), and is widely used as a molecular marker to identify stem cells in embryos and adult tissues (26)(27)(28)(29). In our study, Msi-1 was expressed in five MRT cell lines except TTC642, which originated from a neck mass.…”
Section: Discussionmentioning
confidence: 93%
“…In recent years, the concept of CSC involvement in tumorigenesis has attracted the attention of many researchers. Previous studies have shown that NSC acting as CSC is recognized in CNS (24)(25)(26)(27)(28)(29). In the present study, we examined the expression of NSC markers such as CD133, nestin and Msi-1 before and after 4-HPR induced differentiation in MRT cell lines to elucidate the cytological characteristics of MRT cells that are considered to derive from neuroectodermal origin (8,9,12).…”
Section: Introductionmentioning
confidence: 99%
“…A disease of great relevance to Msi1 is cancer, because many carcinoma cells are of epithelial stem cell lineage (48), expressing Msi1 protein. Strong expression of the Msi1 protein has been observed in many tumors, such as glioma (25), hepatoma (26), colorectal adenoma (27,49), teratoid/rhabdoid tumors in eye (50), non-small cell lung cancer (51), retinoblastoma (52), medulloblastoma (53,54), ependymoma (53), endometrial carcinoma (55), neurocytoma (56), glioblastoma (57), cervical carcinoma (58), etc. Although the exact function of Msi1 in these cancer cells remains unclear, knockdown of Msi1 by using siRNA resulted in tumor growth arrest in colon adenocarcinoma xenografts transplanted in athymic nude mice, reduced cancer cell proliferation, and increased apoptosis (59).…”
Section: Msi1 and Diseasesmentioning
confidence: 99%